(x - 5)(x - 1) + (x - 3)(x - 5) = 0
giải pt
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(x+1\right)^2-3\left(x+1\right)=0\)
\(\Leftrightarrow\left(x+1\right)\left[\left(x+1\right)-3\right]=0\)
\(\Leftrightarrow\left(x+1\right)\left(x-2\right)=0\)
\(\Leftrightarrow\left[{}\begin{matrix}x+1=0\\x-2=0\end{matrix}\right.\)
\(\Leftrightarrow\left[{}\begin{matrix}x=-1\\x=2\end{matrix}\right.\)
1:
a: =>(|x|+4)(|x|-1)=0
=>|x|-1=0
=>x=1; x=-1
b: =>x^2-4>=0
=>x>=2 hoặc x<=-2
d: =>|2x+5|=2x-5
=>x>=5/2 và (2x+5-2x+5)(2x+5+2x-5)=0
=>x=0(loại)
a: \(\Leftrightarrow\left[{}\begin{matrix}3x+2=4\\3x+2=-4\end{matrix}\right.\Leftrightarrow\left[{}\begin{matrix}x=\dfrac{2}{3}\\x=-2\end{matrix}\right.\)
Ta có: \(\dfrac{x-25}{75}+\dfrac{x-15}{85}+\dfrac{x-5}{95}+\dfrac{x-145}{15}=0\)
\(\Leftrightarrow\dfrac{x-25}{75}-1+\dfrac{x-15}{85}-1+\dfrac{x-5}{95}-1+\dfrac{x-145}{15}+3=0\)
\(\Leftrightarrow\dfrac{x-100}{75}+\dfrac{x-100}{85}+\dfrac{x-100}{95}+\dfrac{x-100}{15}=0\)
\(\Leftrightarrow\left(x-100\right)\left(\dfrac{1}{75}+\dfrac{1}{85}+\dfrac{1}{95}+\dfrac{1}{15}\right)=0\)
mà \(\dfrac{1}{75}+\dfrac{1}{85}+\dfrac{1}{95}+\dfrac{1}{15}>0\)
nên x-100=0
hay x=100
Vậy: S={100}
\(\dfrac{x}{\sqrt{x}-1}\ge0\) (ĐK: \(\left\{{}\begin{matrix}x\ge0\\x\ne1\end{matrix}\right.\))
\(\Leftrightarrow\left\{{}\begin{matrix}\left\{{}\begin{matrix}x< 0\\\sqrt{x}-1< 0\end{matrix}\right.\\\left\{{}\begin{matrix}x\ge0\\\sqrt{x}-1\ge0\end{matrix}\right.\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}\left\{{}\begin{matrix}x< 0\\x< 1\end{matrix}\right.\\\left\{{}\begin{matrix}x\ge0\\x\ge1\end{matrix}\right.\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x< 0\left(ktm\right)\\x\ge1\end{matrix}\right.\) (mà \(x\ne1\))
\(\Leftrightarrow x>1\)
a,\(\left(x-4-5\right)\left(x-4+5\right)=0\Leftrightarrow\left(x-9\right)\left(x+1\right)=0\Leftrightarrow x=9;x=-1\)
b, \(\left(x-3-x-1\right)\left(x-3+x+1\right)=0\Leftrightarrow2x-2=0\Leftrightarrow x=1\)
c, \(\left(x^2-4\right)\left(2x-3\right)-\left(x^2-4\right)\left(x-1\right)=0\)
\(\Leftrightarrow\left(x^2-4\right)\left(2x-3-x+1\right)=0\Leftrightarrow\left(x-2\right)\left(x+2\right)\left(x-2\right)=0\Leftrightarrow x=-2;x=2\)
d, \(\left(3x-7\right)^2-\left(2x+2\right)^2=0\Leftrightarrow\left(3x-7-2x-2\right)\left(3x-7+2x+2\right)=0\)
\(\Leftrightarrow\left(x-9\right)\left(5x-5\right)=0\Leftrightarrow x=1;x=9\)
a) Ta có: 4x-20=0
⇔4x=20⇔4x=20
hay x=5
Vậy: S={5}
b) Ta có: 2x+x+12=02x+x+12=0
⇔3x+12=0⇔3x+12=0
⇔3x=−12⇔3x=−12
hay x=-4
\(\dfrac{1}{\left(x-1\right)\left(x-2\right)}+\dfrac{1}{\left(x-2\right)\left(x-3\right)}+\dfrac{1}{\left(x-3\right)\left(x-4\right)}+\dfrac{1}{\left(x-4\right)\left(x-5\right)}+\dfrac{1}{\left(x-5\right)\left(x-6\right)}=\dfrac{1}{10}\)
\(\Leftrightarrow\dfrac{1}{x-1}-\dfrac{1}{x-2}+\dfrac{1}{x-2}-\dfrac{1}{x-3}+\dfrac{1}{x-3}-....+\dfrac{1}{x-5}-\dfrac{1}{x-6}=\dfrac{1}{10}\)
\(\Leftrightarrow\dfrac{1}{x-1}-\dfrac{1}{x-6}=\dfrac{1}{10}\Leftrightarrow\dfrac{x-6-x+1}{\left(x-1\right)\left(x-6\right)}=\dfrac{1}{10}\)
\(\Leftrightarrow x^2-7x+56=0\Leftrightarrow x^2-2.\dfrac{7}{2}x+\dfrac{49}{4}+\dfrac{175}{4}=\left(x-\dfrac{7}{2}\right)^2+\dfrac{175}{4}>0\)
Vậy phương trình vô nghiệm
(x-5)(x-1)+(x-3)(x-5)=0
<=> (x-5)(x-1+x-3)=0
<=> (x-5)(2x-4)=0
\(\Leftrightarrow\orbr{\begin{cases}x-5=0\\2x-4=0\end{cases}\Leftrightarrow\orbr{\begin{cases}x=5\\2x=4\end{cases}\Leftrightarrow}\orbr{\begin{cases}x=5\\x=2\end{cases}}}\)
Vậy x={5;2}
(x-5)(x-1)+(x-3)(x-5)=0
=>(x-5)(x-1+x-3)=0
=>(x-5)(2x-4)=0
\(\Rightarrow\hept{\begin{cases}x-5=0\\2x-4=0\end{cases}\Rightarrow\hept{\begin{cases}x=5\\2x=4\end{cases}\Rightarrow}}\).....